Ulam-Hyers Stability Results for Fixed Point Problems via --Contractive Mapping in ()-Metric Space - Monica-Felicia Bota; Erdal Karapınar; Oana Mleşniţe (Abstract and Applied Analysis)
We will investigate some existence, uniqueness, and Ulam-Hyers stability results for fixed point problems via --contractive mapping of type-() in the framework of -metric spaces. The presented theorems extend, generalize, and unify several results in the literature, involving the results of Samet et al. (2012).